The Relationship Between Mother’s Education and The Level of Knowledge About Child Malocclusion - Wardhani, Nandhita Ayu; Yusra, Yohana (Journal of Indonesian Dental Association, 2022)
Introduction: Malocclusion is a dental and oral health problem that often occurs in children and adolescents. The prevalence of dental and mouth problems in East Kalimantan Province is still quite high with the largest age group being 5-9 years. Knowledge about dental and oral health, especially in the aspect of child malocclusion, is related to the level of education of parents. Objective: To determine the relationship between the education of the mother of a student at SDN 005 Penajam, East Kalimantan and the level of knowledge about child malocclusion. Methods: using an analytic observational method with a cross-sectional, the instrument used was a modified questionnaire from Pravara Institute of Medical Sciences & Rural Dental College, Loni, India. The research population was female students at SDN 005 Penajam, East Kalimantan. Sampling using total sampling technique. Results: from 133 respondents, 60% (n=24) of mothers with tertiary education had good knowledge of malocclusion, 39.02% (n=16) of mothers with secondary education and 48.08% (n=25) of mothers with education have less knowledge about malocclusion. There is a relationship between the education of the mothers of SDN 005 Penajam, East Kalimantan and the level of knowledge about malocclusion in children (p=0.000) and r=0.371 (weak correlation strength). Conclusion: Based on the results of this study it can be concluded that there is a relationship between the education of the mothers of students at SDN 005 Penajam, East Kalimantan and the level of knowledge about child malocclusion (p=0.000). The higher the education the better the results of knowledge. By having good knowledge about malocclusion, mothers can take preventive, curative, and rehabilitative actions so as to reduce the prevalence of malocclusion in children.